Daily versus three-times-weekly azithromycin in Chinese patients with non-cystic fibrosis bronchiectasis: protocol for a prospective, open-label and randomised controlled trial - Jing Li; Fei Chen; Wei Xiao; Feng Li; Lan Chen; Ting He; Yanxiong Mao; Aiping Zou; Bo Fan; Weihao Ni; Huimin You; Wenjiang Fu (BMJ Open)
Introduction Non-cystic fibrosis bronchiectasis (NCFB) brought a heavy healthcare burden worldwide. Macrolide maintenance therapy was proved to be helpful in reducing exacerbation of NCFB. However, the optimal dosing regimens of macrolides have not been determined, and its efficacy in Chinese NCFB population has not been validated. This protocol describes a head-to-head clinical trial designed to compare the efficacy of two dosing regimens of azithromycin in Chinese NCFB population.Methods and analysis This prospective, open-label and randomised controlled trial will be conducted in the First People’s Hospital of Jiashan, China. Eligible patients with high-resolution CT defined NCFB will be randomly divided into three groups, which will receive either 250 mg daily azithromycin, or 500 mg three-times-weekly azithromycin or no treatment for 6 months. They will be followed up for another 6 months without treatment. The primary outcome is the mean rate of protocol-defined pulmonary exacerbation at 6 months.Ethics and dissemination Ethical approval was obtained from the First People’s Hospital of Jiashan Ethics Committee. The findings will be disseminated in peer-reviewed publications.Trial registration number ChiCTR2100052906.